Atypical functional hierarchy contributed to the tinnitus symptoms in patients with vestibular schwannoma - Lin, Jiaji; You, Na; Li, Xiaolong; Huang, Jiayu; Lu, Haoxuan; Hu, Jianxing; Zhang, Jun; Lou, Xin (Frontiers in Neuroscience, 2023)
Objective Tinnitus is frequently found in patients with vestibular schwannoma (VS), but its underlying mechanisms are currently unclear. Methods Both preoperative (VSpre) and postoperative (VSpost) functional MR images were collected from 32 patients with unilateral VS and matched healthy controls (HCs). Connectome gradients were generated for the identification of altered regions and perturbed gradient distances. Tinnitus measurements were conducted for predictive analysis with neuroimaging–genetic integration analysis. Results There were 56.25% of preoperative patients and 65.63% of postoperative patients suffering from ipsilateral tinnitus, respectively. No relevant factors were identified including basic demographics info, hearing performances, tumor features, and surgical approaches. Functional gradient analysis confirmed atypical functional features of visual areas in VSpre were rescued after tumor resection, while the gradient performance in the postcentral gyrus continues to maintain (VSpost vs. HC : P = 0.016). The gradient features of the postcentral gyrus were not only significantly decreased in patients with tinnitus (PFDR = 0.022), but also significantly correlated with tinnitus handicap inventory (THI) score (r = −0.30, P = 0.013), THI level (r = −0.31, P = 0.010), and visual analog scale (VAS) rating (r = −0.31, P = 0.0093), which could be used to predict VAS rating in the linear model. Neuropathophysiological features linked to the tinnitus gradient framework were linked to Ribosome dysfunction and oxidative phosphorylation. Conclusion Altered functional plasticity in the central nervous system is involved in the maintenance of VS tinnitus.